Effect of Azotobacter and Nitrogen Fertilizer Levels on Agro-physiological Traits and Yield of Safflower (Carthamus tinctorius L.) Genotypes under Different Moisture Conditions - Abbas Soleimanifard; Mani Mojaddam; Shahram Lack; Mojtaba Alavifazel (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī, 2024)
This study was to investigate the phenological, physiological traits, seed yield and oil yield of six safflower genotypes under drought stress and non-stress conditions in two independent experiments. Each of the experiment was a factorial with randomized complete block design with three replications during cropping seasons of 2015-16 and 2016-17 at Sarabela Agricultural Research Station in ILAM province. In one experiment under non stress condition, irrigation was based on the need of the plant, while the in the other experiment, plant growth was as rainfed where rainfalls was enough. The total amount of precipitation during the plant growth period in 2015-16 and 2016-17 were 410.7 and 388.5 mm, respectively, but it occurred with inappropriate ditribution during the growing season. Experimental treatments consisted of six  safflower genotypes plus inoculation of seeds with Azotobacter and use of urea fertilizer application with four levels: 1- no fertilizer application (as control), 2- Azotobacter seed inoculation, 3- Azotobacter seed inoculation + 50% nitrogen from urea source and 4- to 100% nitrogen from urea fertilizer based on soil testing recommendation. The results showed that nitrogen source and genotype were significantly affected all traits both under drought and non-stress conditions. Under drought stress conditions, the highest grain yield belonged to Sina genotype by using 100% nitrogen fertilizer and Azotobacter + 50% nitrogen fertilizer treatments (with mean yield of 1408 and 1336 kg.ha-1 reapectively), which were not significantly different. Under non-stress conditions, the highest grain, with mean yield of 2185 kg.ha-1, was attributed to PI-306974 genotype with 100% nitrogen fertilizer treatment. Thus, this genotype, under non-stress conditions, by using 100% nitrogen fertilizer for maximum yield of safflower and under drought stress, it was Sina genotype by using 50% nitrogen fertilizer with Azotobacter can be recommanded to the experimental region.